ECONOMIC DEVELOPMENT OF TRANSMIGRATION COMMUNITIES IN MUKTI SARI VILLAGE, TAPUNG DISTRICT, KAMPAR REGENCY (1988 – 2023): Perkembangan Perekonomian Masyarakat Transmigrasi Di Desa Mukti Sari Kecamatan Tapung Kabupaten Kampar (1988 – 2023) - Tri Andini; Ahmal Ahmal; Yuliantoro Yuliantoro (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study discusses the Economic Development of the Transmigration Community in Mukti Sari Village, Tapung District, Kampar Regency (1988 - 2023). The purpose of this study is to determine the early history of arrival, Economic Improvement, the impact of the Independent Energy Village program on the economy and the Transmigration Community of Mukti Sari Village. This study uses a historical approach that includes the stages of heuristics, verification, interpretation, and historiography. This research was conducted in Mukti Sari Village, Tapung District, Riau Province. This study shows that the entry of people who participated in the transmigration program in Mukti Sari Village, Tapung District, Kampar Regency took place in 1988 when it was the New Order period which was included in Repelita IV. This is based on information provided by the first transmigration community who occupied the Mukti Sari village area which was still included in (UPT). Mukti Sari village is the oldest village, because in the village it was the first village to become a placement area for Transmigrants in 1988 and was the first transmigration unit. The current population of Mukti Sari village is approximately 5,000 people.